Case Report: Tuberculosis with Pericardial Effusion in Children - Muhammad Ali Shodikin (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Background. Tuberculosis pericardial effusion is a rare case in the developed countries. This may cause serious and deadly impact if not diagnosed and treated properly. Appropriates diagnosis and treatment of tuberculosis pericardial effusion can prevent mortality. Case. A 14-years-old boy was admitted with tightness of breath, chest pain, and abdominal enlargement. Chest X-ray revealed heart enlargement and echocardiography showed a massive pericardial effusion. The diameter of induration of tuberculin skin test was 14 mm. This patient was diagnosed as tuberculosis pericardial effusion and showed complete recovery after paricardiocentesis and anti-tuberculosis drugs administration for 12 month. Conclusion. Tuberculosis pericardial effusion should be remembered in cases of tightness of breath with chest x ray revealing heart enlargement. Adequate treatment by pericardiocentesis and anti-tuberculosis drugs can completely cure this disease.